Gugatan Citizen Lawsuit dalam Perkara Lingkungan Hidup di Indonesia: Eksistensi dan Perkembangan - Pramana, Willy Eka; Awiati, Wiwiek (Simbur Cahaya, 2024)
Citizen Lawsuit is a mechanism for citizen-initiated legal actions that has developed within the common law legal system, which is currently widely adopted by countries with civil law legal systems. Citizen Lawsuit (CLS) has been recognized in the judicial system of Indonesia since the first ruling, Case Number 28/PDT.G/2003/PN.JKT.PST, within the scope of general jurisdiction. The existence of Citizen Lawsuit in environmental law became apparent following the issuance of Chief Justice Decree Number 36/KMA/SK/II/2013 concerning guidelines for handling environmental cases. This research delves into the evolution and implementation of Citizen Lawsuit in Indonesia, along with an analysis of the rulings related to Citizen Lawsuit, specifically the judgments from the District Court of Samarinda, Case Number 55/PDT.G/2013/PN.SMDA, and the District Court of Central Jakarta, Case Number 374/PDT.G/LH/2019/PN JKT. PST. The study aims to explore the constraints related to the competence of the judiciary and fundamental differences in handling CLS environmental cases in Indonesia following the enactment of Supreme Court Regulation Number 1 of 2023 on Guidelines for Adjudicating Environmental Cases. It also seeks to analyse the rulings that have revitalized the existence of CLS. The research method employed in this study is a juridical-normative approach